2010
DOI: 10.1212/wnl.0b013e3181cef7e3
|View full text |Cite
|
Sign up to set email alerts
|

11 C-PIB binding is increased in patients with cerebral amyloid angiopathy–related hemorrhage

Abstract: (11)C-Pittsburgh compound B (PIB) binding is moderately increased in most patients with probable cerebral amyloid angiopathy (CAA)-related intracerebral hemorrhage. The distribution may differ from that seen in Alzheimer disease. (11)C-PIB PET may assist in the in vivo diagnosis of CAA and serve as a surrogate marker for future therapeutic studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
155
1
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 145 publications
(169 citation statements)
references
References 39 publications
11
155
1
2
Order By: Relevance
“…This interpretation is consistent with extensive previous reports of associations between PiB retention and the hemorrhagic and ischemic markers of CAA. [7][8][9][10][11][12][13][14]36 The observation of increased relative florbetapir retention in occipital cortex (even after adjustment for global SUVR) further supports this interpretation, as this pattern parallels the posterior predominance of CAA pathology. 9,10,37 Some of the observed florbetapir retention likely also reflects accompanying parenchymal AD pathology, which often co-occurs with CAA (despite our restriction to cognitively normal patients with MMSE 29-30).…”
Section: Resultsmentioning
confidence: 79%
See 1 more Smart Citation
“…This interpretation is consistent with extensive previous reports of associations between PiB retention and the hemorrhagic and ischemic markers of CAA. [7][8][9][10][11][12][13][14]36 The observation of increased relative florbetapir retention in occipital cortex (even after adjustment for global SUVR) further supports this interpretation, as this pattern parallels the posterior predominance of CAA pathology. 9,10,37 Some of the observed florbetapir retention likely also reflects accompanying parenchymal AD pathology, which often co-occurs with CAA (despite our restriction to cognitively normal patients with MMSE 29-30).…”
Section: Resultsmentioning
confidence: 79%
“…6 One of the exciting advances in CAA research has been the demonstration of the ability of Pittsburgh compound B (PiB), originally designed to detect plaque amyloid in Alzheimer disease (AD), to label vascular amyloid as well. [7][8][9][10] This PET tracer was shown to bind vascular amyloid by radiologic-pathologic correlation in both the common sporadic form of CAA and Iowa-type hereditary CAA, a form of the disorder with little or no plaque deposits of fibrillar Ab. 11,12 Amyloid imaging using PiB-PET has already made important contributions to our understanding of CAA-related hemorrhagic and ischemic disease mechanisms, 2,7,8,13,14 such as prediction of future hemorrhages.…”
Section: Classification Of Evidencementioning
confidence: 99%
“…11 C-PiB is also elevated in subjects diagnosed with cerebral amyloid angiopathy (66,67), showing a distribution similar to that in AD patients except that slightly greater binding may be seen in the occipital cortex.…”
Section: C-pib In Other Conditionsmentioning
confidence: 69%
“…As already pointed out, previous similar studies did not have such homogeneous CAA samples, which may explain their reported significant difference in wcDVR between patients and HAMCs. 6,10,12 In addition, in the Ly et al 10 study, 2/12 patients did not have T2* scans, and whether PiB þ HCs were excluded or not remains unclear. All our patients were on at least one, and several on up to four oral medications ( Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…However, the quantitative analysis may perform better, given previous reports that suggest significantly higher occipital/frontal ratio in CAA as compared with AD. 6,10 We tested this hypothesis in a post hoc analysis using a sample of seven probable AD patients 39 (mean age: 66, range 59 to 73) from our center's database, which recovered the expected difference in calcarine/frontal DVR (0.94 ± 0.10 vs. 0.86 ± 0.07 in CAA and AD groups, respectively; one-tailed P ¼ 0.027). Although preliminary, these findings support the idea that amyloid imaging may be of use in diagnosing suspected CAArelated ICH according to the above two-step procedure according to a quantitative analysis.…”
Section: Discussionmentioning
confidence: 99%